2024
DOI: 10.3390/sym16020224
|View full text |Cite
|
Sign up to set email alerts
|

Large Deflection Geometrically Nonlinear Bending of Porous Nanocomposite Cylindrical Panels on Elastic Foundation

Jin-Rae Cho

Abstract: Large deflection nonlinear bending of functionally graded (FG) porous cylindrical panels reinforced with graphene platelets (GPLs) on a Pasternak-type elastic foundation is examined by developing a reliable and effective 2D meshfree-based nonlinear numerical method. The large displacement field is express by the first-order shear deformation theory (FSDT) and the von Kármán nonlinearity, and approximated by 2D natural element method (NEM) in conjunction with the stabilized MITC3+ shell concept and the shell su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…It is observed that the frequency ratio becomes uniformly smaller with the increase in , it uniformly increases in proportion to 0 e . However, the extent of decrease becomes smaller as the porosity parameter 0 because the increase in porosity decreases the structural stiffness[54]. But, the frequency ratio…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…It is observed that the frequency ratio becomes uniformly smaller with the increase in , it uniformly increases in proportion to 0 e . However, the extent of decrease becomes smaller as the porosity parameter 0 because the increase in porosity decreases the structural stiffness[54]. But, the frequency ratio…”
mentioning
confidence: 98%
“…However, the extent of decrease becomes smaller as the porosity parameter e 0 increases. Both ω L and ω NL decrease proportionally to e 0 because the increase in porosity decreases the structural stiffness [54]. But, the frequency ratio ω NL /ω L may increase with increasing e 0 because the denominator ω L decreases in proportion to e 0 .…”
mentioning
confidence: 99%